Analysis of the Problems of Islamic Religious Education and Moral Education at SMP Negeri 18 Medan - Muhammad Syawal Karo Karo; Arlina Arlina (MUADDIB Jurnal Kependidikan dan Keislaman, 2023)
This research was conducted by looking at the background of the development of the times that have been very rapidly developed, then coupled with the majority non-Muslim school environment and also minimal religious extracurricular so that, of course, all of that can affect the learning of Islamic Religious Education in the school. Therefore, the purpose of this research is to find out what and how the problems that exist in learning Islamic Religious Education at SMP Negeri 18 Medan include how the issue of educators, the problem of students, the problem of curriculum, the problem of extracurricular and the problem of facilities and infrastructure. This research uses qualitative research methods and uses a descriptive approach. As for this research using primary and secondary data types, the data analysis techniques used are data collection, reduction, display, and conclusion drawing/verification. The results of this study will also provide knowledge to readers, especially for prospective PAI teachers, and also provide points as school evaluation material to improve PAI learning. The results of this study indicate that several problems occur in SMP Negeri 18 Medan related to learning Islamic Religious Education. The situation is an obstacle, difficulty, and challenges faced in the PAI learning process. The problem lies in the learning component itself, among other things, the issue of educators, the problem of students, the problem of curriculum, the problem of extracurricular, and the problem of facilities and infrastructure.